2021
DOI: 10.3390/foods10020243
|View full text |Cite
|
Sign up to set email alerts
|

Disaccharide Type Affected Phenolic and Volatile Compounds of Citrus Fiber-Blackberry Cream Fillings

Abstract: The food industry is continuously developing ingredients, processing methods and packaging materials to improve the quality of fruit products. The aim of this work was to study the possibility of using citrus fiber in the preparation of blackberry cream fillings in combination with disaccharides (sucrose, maltose and trehalose). Evaluations of the phenolics, proanthocyanidins, antioxidant activity, color and volatiles of blackberry cream fillings were conducted after preparation and after three months of stora… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 58 publications
0
7
0
Order By: Relevance
“…In a study conducted by Vukoja et al [ 22 ], the addition of disaccharides (sucrose, maltose, trehalose) during the manufacture of juice and cream from blackberries had a significant impact on in the concentrations of most identified volatile compounds within each chemical group of compounds, i.e., alcohols, acids, aldehydes and ketones, and terpenes. Sucrose addition significantly increased concentrations of the analyzed volatiles compared to other products made with the addition of other sugars [ 22 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In a study conducted by Vukoja et al [ 22 ], the addition of disaccharides (sucrose, maltose, trehalose) during the manufacture of juice and cream from blackberries had a significant impact on in the concentrations of most identified volatile compounds within each chemical group of compounds, i.e., alcohols, acids, aldehydes and ketones, and terpenes. Sucrose addition significantly increased concentrations of the analyzed volatiles compared to other products made with the addition of other sugars [ 22 ].…”
Section: Resultsmentioning
confidence: 99%
“…In a study conducted by Vukoja et al [ 22 ], the addition of disaccharides (sucrose, maltose, trehalose) during the manufacture of juice and cream from blackberries had a significant impact on in the concentrations of most identified volatile compounds within each chemical group of compounds, i.e., alcohols, acids, aldehydes and ketones, and terpenes. Sucrose addition significantly increased concentrations of the analyzed volatiles compared to other products made with the addition of other sugars [ 22 ]. Moreover, in cocoa products manufactured with various sugars (added in a total amount of 80%), the addition of sucrose contributed to increased concentrations of most identified volatile compounds compared to other added sugars, except for the concentration of aldehydes and ketones, which was similar [ 23 ].…”
Section: Resultsmentioning
confidence: 99%
“…The unique structure of trehalose enables trehalose to interact with both hydrophilic and hydrophobic molecules [ 57 ]; thus, this property could be the reason for the differences between the sucrose and trehalose microparticles. The differences caused by disaccharide types in fruit samples were proven in several studies [ 33 , 35 , 36 , 37 , 39 , 58 ], and in most cases, trehalose had a more positive effect on phenolics and antioxidant activity.…”
Section: Discussionmentioning
confidence: 95%
“…Sucrose is a commonly used saccharide in fruit product formulations, while the use of trehalose in formulations of fruit products is increasing in frequency. The positive influence of trehalose on volatiles and phenolics in different freeze-dried fruit products has been proven in several studies [ 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 ], therefore we wanted to determine whether a similar effect could be achieved in combination with apple fibers. An additional benefit of trehalose is its slow digestion, which results in a lower glycemic index, with a lower insulin release compared to sucrose [ 40 ].…”
Section: Introductionmentioning
confidence: 99%
“…Sucrose is established as a commonly used saccharide in fruit product formulations, while the utilization of trehalose in the formulation of fruit products has been increasing. Sucrose and trehalose’s impact on volatiles and phenolics in different fruit products has been investigated in numerous studies [ 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 ]. It was concluded that disaccharides’ effect on fruit product quality depended on its type as well as the amount.…”
Section: Introductionmentioning
confidence: 99%